Bone-marrow transplantation has a limited role in prolonging second marrow remission in childhood lymphoblastic leukaemia. - Chessells, J; Rogers, D; Leiper, A; Blacklock, H; Plowman, P; Richards, S; Levinsky, R; Festenstein, H (1986)
Fifty-three children with acute lymphoblastic leukaemia whose first complete remission ended in bone-marrow relapse received similar reinduction and consolidation therapy. Thirteen had an HLA-compatible sibling donor and were eligible to receive a bone-marrow transplant (BMT); five survive, all off treatment in continuing remission. Forty had no donor and received further chemotherapy; sixteen survive, twelve in remission and six off treatment. After 1-5.5 years' follow-up from relapse, there is no significant difference in survival between the groups. The major obstacle to success is marrow relapse which occurred in two eligible patients before BMT could be carried out. The lengths of first and second remissions in both groups were significantly correlated. Morbidity in survivors was substantial. The scope of BMT as retrieval therapy for ALL is limited by the instability of second remissions; this difficulty will not be overcome by increasing the number of potential donors or the use of autologous marrow.